2016
DOI: 10.5897/ajpp2016.4686
|View full text |Cite
|
Sign up to set email alerts
|

Euterpe oleracea Mart. (aai): an old known plant with a new perspective

Abstract: The açai (Euterpe oleracea Mart) fruit pulp is extensively used in Brazil as food among other uses. The health benefits of açai are largely reported by the Amazon inhabitants. Nonetheless, just a few pharmacological and toxicological studies were made to probe the innocuousness and the safety of the use of this product. The aims of this work were to update knowledge about the chemical composition, pharmacological and toxicological studies of the fruits and to identify possible vacuum of knowledge in the use, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Some comprehensive studies have shown different biological activities of açaí, such as anti-lipidemic, neuroprotective, hypocholesterolemic, therapeutic, anti-inflammatory, and anti-cancer properties [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some comprehensive studies have shown different biological activities of açaí, such as anti-lipidemic, neuroprotective, hypocholesterolemic, therapeutic, anti-inflammatory, and anti-cancer properties [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%